The Advancing of Selenium Nanoparticles Against Infectious Diseases - Lin, Wensen; Zhang, Junai; Xu, Jun-Fa; Pi, Jiang (Frontiers in Pharmacology, 2021)
Infectious diseases, caused by the direct exposure of cellular or acellular pathogens, are found to be closely associated with multiple inflammation and immune responses, keeping one of the top threats to human health. As an indispensable trace element, Selenium (Se) plays important roles in antioxidant defence and redox state regulation along with a variety of specific metabolic pathways. In recent decades, with the development of novel nanotechnology, Selenium nanoparticles (Se NPs) emerged as a promising agent for biomedical uses due to their low toxicity, degradability and high bioavailability. Taking the advantages of the strong ability to trigger apoptosis or autophagy by regulating reactive oxygen species (ROS), Se NPs have been widely used for direct anticancer treatments and pathogen killing/clearance in host cells. With excellent stability and drug encapsulation capacity, Se NPs are now serving as a kind of powerful nano-carriers for anti-cancer, anti-inflammation and anti-infection treatments. Notably, Se NPs are also found to play critical roles in immunity regulations, such as macrophage and T effector cell activation, which thus provides new possibilities to achieve novel nano-immune synergetic strategy for anti-cancer and anti-infection therapies. In this review, we summarized the progress of preparation methods for Se NPs, followed by the advances of their biological functions and mechanisms for biomedical uses, especially in the field of anti-infection treatments. Moreover, we further provide some prospects of Se NPs in anti-infectious diseases, which would be helpful for facilitating their future research progress for anti-infection therapy.